2020
DOI: 10.1242/jcs.242412
|View full text |Cite
|
Sign up to set email alerts
|

PTPN23 binds the dynein adaptor BICD1 and is required for endocytic sorting of neurotrophin receptors

Abstract: Signalling by target-derived neurotrophins is essential for the correct development of the nervous system and its maintenance throughout life. Several aspects concerning the lifecycle of neurotrophins and their receptors have been characterised over the years, including the formation, endocytosis and trafficking of signalling-competent ligandreceptor complexes. However, the molecular mechanisms directing the sorting of activated neurotrophin receptors are still elusive. Previously, our laboratory identified Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…Hence, we conclude that the retrograde trafficking defects occur after the initial endocytosis of CTB/TrkB. Indeed, perturbations in retrograde transport of signalling endosomes in Endophilin triple KO neurons or inhibition of dynein motor proteins result in similar cellular phenotypes and reduced survival, albeit less pronounced, as presented in this study (Burk et al, 2017;Budzinska et al, 2020). Hence, defects in retrograde transport of signalling endosomes provide a plausible explanation for the observed abnormalities in CTB transport and retrograde TrkB trafficking, and also for the reduced Golgi size in Munc18-1 KO neurons.…”
Section: Anterograde/retrograde Trafficking Imbalance Explains Golgi Abnormalitiessupporting
confidence: 68%
See 2 more Smart Citations
“…Hence, we conclude that the retrograde trafficking defects occur after the initial endocytosis of CTB/TrkB. Indeed, perturbations in retrograde transport of signalling endosomes in Endophilin triple KO neurons or inhibition of dynein motor proteins result in similar cellular phenotypes and reduced survival, albeit less pronounced, as presented in this study (Burk et al, 2017;Budzinska et al, 2020). Hence, defects in retrograde transport of signalling endosomes provide a plausible explanation for the observed abnormalities in CTB transport and retrograde TrkB trafficking, and also for the reduced Golgi size in Munc18-1 KO neurons.…”
Section: Anterograde/retrograde Trafficking Imbalance Explains Golgi Abnormalitiessupporting
confidence: 68%
“…The impairment in retrograde transport might not only provide an explanation for the Golgi abnormalities, but also for the fact that Munc18-1 KO neurons die. Correct retrograde transport of TrkB is essential for neuronal survival (Reichardt, 2006;Burk et al, 2017), and comparable abnormalities in TrkB-containing endosomes have been reported upon perturbations of the retrograde pathways, leading to defective neurotrophic signalling and reduced neuronal survival (Wan et al, 2008;Budzinska et al, 2020). In addition, enlarged signalling endosomes have directly been linked to neurodegenerative processes (Xu et al, 2016).…”
Section: Defects In Retrograde Pathways Can Explain Degeneration In Munc18-1 Ko Brainsmentioning
confidence: 85%
See 1 more Smart Citation
“…To further investigate the impaired retrograde pathways, we examined the retrograde endosomal pathway of TrkB using live labelling with a TrkB antibody (Barford et al, 2017; Budzinska et al, 2020; Carrodus et al, 2014). First, TrkB surface expression was assessed in fixed neurons prior to permeabilization.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, correct retrograde signalling of TrkB is critical for neuronal survival (Burk et al, 2017;Reichardt, 2006). Comparable abnormalities in TrkBcontaining endosomes have been reported upon perturbations of the retrograde pathways, leading to defective neurotrophic signalling and reduced neuronal survival (Budzinska et al, 2020;Wan et al, 2008).…”
Section: Defects In Retrograde Pathways Can Explain Degeneration In Munc18-1 Ko Brainsmentioning
confidence: 99%